2003
DOI: 10.1103/physrevlett.90.135504
|View full text |Cite
|
Sign up to set email alerts
|

Growth of Three-Shell Onionlike Bimetallic Nanoparticles

Abstract: We show by molecular dynamics simulations on three systems (B/A=Pd/Ag, Cu/Ag, and Ni/Ag) that three-shell metallic nanoparticles made by a core of a metal A, an intermediate shell of metal B and an external shell of metal A (A-B-A nanoparticles) can be grown by deposition of B atoms onto an A core. The growth of the intermediate B shell is triggered by the fact that the most favorable positions for isolated B impurities inside A clusters are located just one layer below the cluster surface.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
230
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 276 publications
(248 citation statements)
references
References 19 publications
17
230
0
1
Order By: Relevance
“…Also, even though this is not our prime interest here, it should be noted that kinetic factors can be crucial in this problem. 13 In particular, Vach and coworkers have found from experiments and simulations of mixed rare-gas clusters that some anomalous enrichment effects could be observed due to the growth by pick-up of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…Also, even though this is not our prime interest here, it should be noted that kinetic factors can be crucial in this problem. 13 In particular, Vach and coworkers have found from experiments and simulations of mixed rare-gas clusters that some anomalous enrichment effects could be observed due to the growth by pick-up of these systems.…”
Section: Introductionmentioning
confidence: 99%
“…46 The synthesis of monodisperse Au-Ag nanoalloy particles in a one-pot approach was reported for the first time by Sun et al 47 The composition of Au-Ag alloy was controlled through the ratio of the precursors and growth time during the synthesis. For example, with 2 mmol of AgNO 3 , 0.2 mmol of HAuCl 4 , and a growth time of 1 h (at 120 1C), Au 0.60 Ag 0.40 NPs were obtained. Oleylamine was used as the surfactant and was readily removed after synthesis.…”
Section: Preparation Of Au-ag Nanoalloy Systemsmentioning
confidence: 99%
“…The Fe x O y core can be prepared by aqueous (usually co-precipitation) methods, or by thermal decomposition. The gold layer is prepared by attaching Au NP seeds followed by reduction of HAuCl 4 , or sometimes in a single reductive step without using the seed attachment step. From a synthetic perspective a major challenge in the formation of the plasmonic shell is preventing autocatalytic Au reduction/growth, which can result in very thick shells and/or sub-populations of Au NPs.…”
Section: Preparation Of Feo Core Shell Plasmonic-oxide Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, for three-dimensional crystals or two-dimensional islands on solid surfaces formed away from equilibrium, their shapes are away from the prediction of free-energy-based Wulff construction [8][9][10][11][12][13][14]. It has been found that the evolution of Co islands is thermodynamically dominated at 300~600 K, while Pt and Pd islands are kinetically dominated at the same temperature [15].…”
Section: Introductionmentioning
confidence: 99%